Preserving Cultural Heritage via Geographical Indications: Legal Protection of Songket Pandai Sikek in West Sumatra - Siagian, Abdhy Walid; Arinny, Fadhillah; Ningsih, Mareta Puri Nur Ayu; Putri, Trisna Septyan (Journal of Rural and Regional Innovation Studies, 2025)
Geographical Indications are part of intellectual property rights by giving importance to an area to indicate the area of ​​an item and product, especially in providing protection. Indigenous peoples in the West Sumatra region have a product with high economic value based on local cultural values, referred to as crafts traditional Songket Pandai Sikek. However, the Songket Pandai Sikek copyright does not yet have an explicit guarantee of legal certainty, so legal certainty is needed regarding the ownership of the copyright of Songket Pandai Sikek, especially to maintain intellectual property rights for indigenous peoples in West Sumatra. This study uses the Normative Juridical method by using a statute approach and collecting data obtained through library research and data analysis methods using descriptive-analytical methods. Required participation and optimal efforts from all parties to provide legal certainty for the Songket Pandai Sikek copyright ownership through registering the Songket Geographical Indications